RINT1 bi-allelic variations cause infantile-onset recurrent acute liver failure and skeletal abnormalities - Cousin, Margot; Conboy, Erin; Wang, Jian-She; Lenz, Dominic; Schwab, Tanya L.; Williams, Monique; Abraham, Roshini S.; Barnett, Sarah; El-Youssef, Mounif; Graham, Rondell P.; Gutierrez Sanchez, Luz Helena; Hasadsri, Linda; et al. (The American journal of human genetics, 2019)
Pediatric acute liver failure (ALF) is life threatening with genetic, immunologic, and environmental etiologies. Approximately half of all cases remain unexplained. Recurrent ALF (RALF) in infants describes repeated episodes of severe liver injury with recovery of hepatic function between crises. We describe bi-allelic RINT1 alterations as the cause of a multisystem disorder including RALF and skeletal abnormalities. Three unrelated individuals with RALF onset ≤3 years of age have splice alterations at the same position (c.1333+1G>A or G>T) in trans with a missense (p.Ala368Thr or p.Leu370Pro) or in-frame deletion (p.Val618_Lys619del) in RINT1. ALF episodes are concomitant with fever/infection and not all individuals have complete normalization of liver function testing between episodes. Liver biopsies revealed nonspecific liver damage including fibrosis, steatosis, or mild increases in Kupffer cells. Skeletal imaging revealed abnormalities affecting the vertebrae and pelvis. Dermal fibroblasts showed splice-variant mediated skipping of exon 9 leading to an out-of-frame product and nonsense-mediated transcript decay. Fibroblasts also revealed decreased RINT1 protein, abnormal Golgi morphology, and impaired autophagic flux compared to control. RINT1 interacts with NBAS, recently implicated in RALF, and UVRAG, to facilitate Golgi-to-ER retrograde vesicle transport. During nutrient depletion or infection, Golgi-to-ER transport is suppressed and autophagy is promoted through UVRAG regulation by mTOR. Aberrant autophagy has been associated with the development of similar skeletal abnormalities and also with liver disease, suggesting that disruption of these RINT1 functions may explain the liver and skeletal findings. Clarifying the pathomechanism underlying this gene-disease relationship may inform therapeutic opportunities.
Gesehen am 26.07.2019